THE IMPACT OF INTEGRATED MARKETING COMMUNICATIONS ON THE QUALITY OF EDUCATIONAL SERVICE STUDY ANALYTICAL FOR THE OPINIONS OF A SAMPLE OF WORKERS IN PUBLIC AND PRIVATE UNIVERSITIES - Researcher L Luma Qays Raoof Al-ZubaIdI; Dr. Abdulnaser Alag Hafedh (Scholar Express Journal, 2022)
The aim of the current research is to shed light on the impact of integrated marketing communications on the quality of educational service. The research adopted the questionnaire as a basic measurement tool for collecting data from the sample in question, which amounted to (130) questionnaires for the research sample in public and private universities, where it was employed to test the main and secondary research hypotheses through the use of a number of statistical methods, most notably (AMOS) . SPSS.V.25 The results of the research proved the validity of most of the hypotheses, and the research reached a set of conclusions, the most prominent of which was that there is a role for integrated marketing communications on the quality of educational service.
Keywords: Integrated Marketing Communications; Educational Service Quality